Efficient Resource Allocation in a Multinucleated City With Intermediate Goods - Hartwick, Philip G.; Hartwick, John M. (Quarterly Journal of Economics, 1974)
I. The resource allocation problem, 341. — II. Commodity flow equilibrium, 344. — III. Transportation sector and land constraints, 345. — IV. The dual problem and producer and consumer equilibrium, 346. — V. A numerical example, 347. — VI. Concluding remarks, 350. — Appendix, 351.